Post-mortem concentrations of drugs determined in femoral blood in single-drug fatalities compared with multi-drug poisoning deaths. (October 2016) - Jones, Alan Wayne; Holmgren, Anita; Ahlner, Johan
Highlights: Reference concentrations of drugs are reported for 13, 963 poisoning deaths. Drugs were determined in autopsy femoral blood samples. Single-drug fatalities were differentiated from multi-drug poisonings. Ethanol, morphine (heroin), propoxyphene, and flunitrazepam where highly prevalent in single-drug intoxications. Mean concentrations of drugs in blood were 2–10 times higher in single-drug fatalities compared with multi-drug poisonings. Abstract: Background: Reference concentrations of drugs in post-mortem femoral blood furnishes useful information when poisoning (intoxication) deaths are investigated. However, few publications compare the concentrations of drugs in single-drug fatalities with multi-drug intoxications. This article attempts to fill this gap in knowledge. Methods: We searched a national forensic toxicology database (TOXBASE) and found N = 13, 963 deaths attributed by pathologists to intoxication by drugs (poisoning). The manner of death, whether accidental, suicidal or undetermined intent, was also available. To compare drug concentrations in living and deceased persons, we used information from people arrested for driving under the influence of drugs (DUID). Results: The percentage of drug intoxication deaths classified as undetermined intent decreased and accidental overdose deaths increased during the study period. In 2010 manner of death was considered accidental, suicidal or undetermined, in 41%, 30% and 28% of victims, respectively. Most of the deceased had taken multiple drugs (mean three drugs/case) and four or more drugs were identified in 35% of deaths. In single-drug fatalities ethanol (1585), morphine (114), citalopram (28), propoxyphene (51), flunitrazepam (70), propiomazine (46), tramadol (20) and zopiclone (15) were most prevalent. Alprazolam and diazepam were common findings in multi-drug deaths, although these benzodiazepines were rarely encountered in mono-drug intoxication deaths. Median blood concentrations were appreciably higher (2–10 fold) in single-drug fatalities compared with multi-drug deaths. The blood concentrations in DUID suspects were mostly lower than in the multi-drug poisoning deaths. Conclusion: This compilation of femoral blood concentrations of drugs in poisoning deaths provides a useful reference material, because we have distinguished between mono-drug intoxication deaths and poisoning with multiple-drugs.